Does Using CobiT Improve IT Solution Proposals? - Marshall,Byron; Curry,Michael; Reitsma,Reindert (AAA Annual Meeting, IS Section, 2010)
The CobiT (Control Objectives for Information and related Technology) framework is designed to help organizations implement IT governance practices by systematically shaping identifiable IT processes to better leverage IT expenditures. The control structure advocated in CobiT embodies governance notions including business alignment, a risk/control perspective, systematic measurement, accountability, and continuous improvement. Despite the rise of internal control regulation, not all organizations have implemented systematic IT controls and many, notably small, organizations may never do so. This study explores whether exposing decision makers to CobiT positively affects the IT solutions they generate. We present a framework (drawn primarily from the structure of CobiT) for identifying normatively better IT plans as measured by application of governance principles. We report on 115 IT solution proposals created by business students. The proposals developed using CobiT more frequently took a risk/control approach, addressed the need for continuous improvement, referred to general IT processes, identified the people who should implement a solution, and proposed more measures of success. Thus, exposing decision makers to a systematic IT governance framework promises to help them generate more comprehensive solutions to IT challenges.
Keywords: Accounting; BIS